Communication Strategy in Promoting City Branding Yogyakarta as Hanacaraka City - Mansur, Suraya; Muhammad, Ameliya (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2024)
Marking the momentum for the revival of the Javanese script, the Governor of the Special Region of Sri Sultan Hamengku Buwono X, proclaimed Yogyakarta as the City of Hanacaraka on International Script Day, September 8, 2021. This research aims to determine the city branding strategy carried out by the Provincial Government of the Special Region of Yogyakarta Culture Department in branding the City of Hanacaraka. The theory used is the city branding hexagon theory by Simon Anholt. This study used a qualitative descriptive approach using the case study method. In this study, the primary data to be used is observation in the form of in-depth interviews directly with informants. The study results show the communication strategy to convey a message about the concept of the City of Hanacaraka was carried out in various ways, the literate village program and a literacy clinic. For the script village, Yogyakarta Culture Department is working with 76 cultural villages. Through the script village, the Javanese script was taught again to the people of Yogyakarta, in order to re-customize the Javanese script. For the script clinic Yogyakarta Culture Department provides a Javanese script converter for transliteration of Javanese script to Latin and vice versa.